The risk of complications of endoscopic procedures in patients with liver cirrhosis - Simon, Krzysztof; Orłowska, Iwona; Pazgan-Simon, Monika (Clinical and Experimental Hepatology, 2017)
Endoscopy methods involve diagnostics as well as therapy. Endoscopic techniques have a small but definite incidence of complication, so endoscopy should not be performed routinely but only on the basis of indication. The typical endoscopic procedures used in diagnostics and therapy of liver cirrhosis are endoscopy of upper and lower gastrointestinal tract. Other techniques are less common. Significance of endoscopy procedures increases in case of chronic progressive liver diseases, independently of etiology, where changes in gastrointestinal tract are observed in 87% of patients.